Bimetallic platinum–bismuth nanoparticles prepared with silsesquioxane for enhanced electrooxidation of formic acid. (13th April 2015) - Chen, Tingting; Ge, Cunwang; Zhang, Yihong; Zhao, Qin; Hao, Furui; Bao, Ning
Abstract Bimetallic platinum–bismuth nanoparticles (Pt-BiNPs) were prepared with octa-(3-amino-propyl) silsesquioxane (OA-POSS) for high-performance electrooxidation of formic acid. Characterization of nanoparticles revealed their homogeneous-phase with blackberry-like morphology when the fraction of Bi was no less than 60%. Their electrocatalytic activity was investigated with cyclic voltammetry and chronoamperograms. The prepared bimetallic Pt-BiNPs displayed larger electrochemical surface areas, better electrocatalytic activity and more favourable durability towards electrocatalytic oxidation of formic acid compared with commercial catalysts. The improvement might be ascribed to the role of OA-POSS as the control agent of morphology and the carrier of electrocatalyst with possible corrosive resistance. This study suggested that silsesquioxane might potentially facilitate preparation of homogeneous-phase nanoscaled catalysts for direct formic acid fuel cell in practical applications.